Evidence for reducing cancer-specific mortality due to screening for breast cancer in Europe: A systematic review - Zielonke, Nadine; Gini, Andrea; Jansen, Erik E.L.; Anttila, Ahti; Segnan, Nereo; Ponti, Antonio; Veerus, Piret; de Koning, Harry J.; van Ravesteyn, Nicolien T.; Heijnsdijk, Eveline A.M.; Veerus, Piret; Anttila, Ahti; et al. (European journal of cancer (1990), 2020)
The aim of this study was to quantify the impact of organised mammography screening on breast cancer mortality across European regions. Therefore, a systematic review was performed including different types of studies from all European regions and stringently used clearly defined quality appraisal to summarise the best evidence. Six databases were searched including Embase, Medline and Web of Science from inception to March 2018. To identify all eligible studies which assessed the effect of organised screening on breast cancer mortality, two reviewers independently applied predefined inclusion and exclusion criteria. Original studies in English with a minimum follow-up of five years that were randomised controlled trials (RCTs) or observational studies were included. The Cochrane risk of bias instrument and the Newcastle–Ottawa Scale were used to assess the risk of bias. Of the 5015 references initially retrieved, 60 were included in the final analysis. Those comprised 36 cohort studies, 17 case–control studies and 7 RCTs. None were from Eastern Europe. The quality of the included studies varied: Nineteen of these studies were of very good or good quality. Of those, the reduction in breast cancer mortality in attenders versus non-attenders ranged between 33% and 43% (Northern Europe), 43%–45% (Southern Europe) and 12%–58% (Western Europe). The estimates ranged between 4% and 31% in invited versus non-invited. This systematic review provides evidence that organised screening reduces breast cancer mortality in all European regions where screening was implemented and monitored, while quantification is still lacking for Eastern Europe. The wide range of estimates indicates large differences in the evaluation designs between studies, rather than in the effectiveness of screening. •Study summarises current evidence of mortality reduction due to mammography screening.•Includes different types of studies, using a methodologically sound quality appraisal.•Impact ranges between 12% and 58% in screening attenders versus non-attenders.•Impact ranges between 4% and 31% in invited versus non-invited women.•Quantification of the actual effects is still lacking for Eastern Europe.•Results fortify that mammography screening reduces mortality from breast cancer.